Pengaruh Edukasi Kesehatan dengan Media Video tentang Cuci Tangan terhadap Pengetahuan Anak untuk Cegah Covid di SDN 3 Tempuran 12B Trimurjo Kabupaten Lampung Tengah Tahun 2023 - Mevia, Dila Artha; Triswanti, Nia; Anggunan, Anggunan; Farich, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Background: Covid-19 is transmitted through droplets (splashes) when talking, coughing and sneezing from people infected with the Coronavirus. In addition, this disease can also be transmitted through physical contact (touch or handshake) with sufferers and touching the face, mouth and nose by hands that are exposed to the Coronavirus. Clean living behavior (PHBS) is one of the prevention of Covid-19, for example, washing hands with soap. Research Methods: Analytical Survey using a cross-sectional approach with 34 samples according to the research criteria. Data collection was carried out in July 2023. This research was conducted at SDN 3 Tempuran, Trimurjo District, Central Lampung Regency, Lampung Province, with data analysis using SPSS 26. Research results: There were 34 samples of research respondents, the highest was in the 11 year age group, namely 12 respondents (35.3%) with an average of 10.21, it was known that there were more women, namely 19 respondents (55.9%). Then the class of respondents was divided into grades 4.5 and 6 and most were found in Grade 6 students, namely 14 respondents (41.2%). The majority of children's knowledge distribution before being given education is low knowledge in 21 respondents (61.8%). While the distribution of children's knowledge after being given education was the majority in high knowledge in 21 respondents (61.8%). The p-value was obtained 0.000 (p-value <0.005). Conclusion: there is the influence of video media on the level of knowledge of handwashing with soap in preventing COVID-19..